Sound Symbolism and Its Syntactic Function in Japanese Post-positional Particles - White, Sean A. (Kansas Working Papers in Linguistics, 1999)
Native speakers of Japanese tend to verbally describe, specify, and qualify human action and natural phenomena by means of words comprised of seemingly abstract sounds, which suggests that there exists in Japanese symbolic meanings in various sounds which underscore the lexical meaning of those words. Based on previous investigations into the nature and meaning of sound in Japanese, this paper shall attempt to broaden the inquiry regarding the possible existence and function of Japanese sound symbolism through an analysis of its relationship with post-nominal particles.